The main results of mineralogical and petrographic studies of limestones from Novoselytske deposit (Ukraine) - Ishkov, Valerii Valeriiovych; Kozii, Yevhen Serhiiovych; Dreshpak, Oleksandr Stanislavovych; Berezniak, Olena Oleksandrivna; Chechel, Pavlo Olehovych; Pashchenko, Pavlo Serhiiovych (Vaiga, 2022)
The paper presents the results of mineralogical and petrographic studies of limestones from Novoselytske deposit (Ukraine). The main attention is paid to the mineral composition and structural features, which determine the geological and commercial type of this mineral, and, consequently, the most rational area of its application. At different scale levels, the features and causes of recrystallization and appearance of zoning have been established.
Keywords: limestone; calcite; recrystallization; zoning